Base mouldings of the jagati of the Chaunsath Yogini Temple - Temples of India Project Team (Jio Institute, 2024)
On the jagati (raised plinth) of the Chaunsath Yogini Temple there are inscriptions probably of masons who contributed to the construction of the temple. Written in the Devanagari script, a few inscriptions contain names like Mahadeva, Asar and Kesanshi.